Children at Risk for Suicide Attempt and Attempt-related Injuries: Findings from the 2007 Youth Risk Behavior Survey - McCarty, Frances (2010)
Purpose: The current study examines the associations between a range of risk factors and reports of suicide attempts and attempts requiring medical care in a nationally representative study of high school students. The goal is to examine sex differences in the risk factors associated with suicide attempts and attempt-related injuries requiring treatment by a health-care provider. Methods: We used data from the 2007 Youth Risk Behavior Survey for students in grades 9-12 to assess the prevalence and risk factors for suicidal behavior, as well as differences in these for boys and girls. Cross-sectional multivariate logistic regression analyses were computed to determine the most important risk factors for suicide attempts and for suicide attempts requiring medical care for the sample overall and also stratified for boys and for girls. Results: Overall, 6.9% of adolescents attempted suicide (9.3% of girls versus 4.6% of boys). Girls were more likely than boys to report a suicide attempt in the past year (Adj.OR=2.89). Among girls, sadness (Adj.OR=5.74), weapon carrying (Adj.OR=1.48), dating violence (Adj.OR=1.60), forced sex (Adj.OR=1.72), and huffing glue (Adj.OR=2.04) were significantly associated with suicide attempts. Among boys, sadness (Adj.OR=10.96), weapon carrying (Adj.OR=1.66), forced sex (Adj.OR=2.60), huffing glue (OR=1.63), hard drug use (Adj.OR=2.18), and sports involvement (Adj.OR=1.52) were significantly associated with suicide attempts. Conclusions: These findings demonstrate similarities and differences in the modifiable risk factors that increase risk for suicide attempts among boys and girls. In terms of the differences between boys and girls, hard drug use and sports involvement may be important factors for suicide-prevention strategies directed specifically towards boys, while dating violence victimization may be an important risk factor to address for girls. Overall, these findings can help guide prevention, clinical practice, and intervention strategies to prevent suicidal behaviors among adolescents